Single cell imaging of human cancer xenografts using adult immune-deficient zebrafish - Yan, Chuan (Nat Protoc, 2020)
Zebrafish are an ideal cell transplantation model. They are highly fecund, optically clear and an excellent platform for preclinical drug discovery studies. Traditionally, xenotransplantation has been carried out using larval zebrafish that have not yet developed adaptive immunity. Larval engraftment is a powerful short-term transplant platform amenable to high-throughput drug screening studies, yet animals eventually reject tumors and cannot be raised at 37 °C. To address these limitations, we have recently developed adult casper-strain prkdc−/−, il2rgα−/− immune compromised zebrafish that robustly engraft human cancer cells for in excess of 28 days. Because the adult zebrafish can be administered drugs by oral gavage or intraperitoneal injection, our model is suitable for achieving accurate, preclinical drug dosing. Our platform also allows facile visualization of drug effects in vivo at single cell resolution over days. Here, we describe the procedures for xenograft cell transplantation into the prkdc−/−, il2rgα−/− model, including refined husbandry protocols for optimal growth and rearing of immune suppressed zebrafish at 37 °C; optimized intraperitoneal and periocular muscle cell transplantation; and epifluorescence and confocal imaging approaches to visualize the effects of administering clinically relevant drug dosing at single cell resolution in vivo. Following identification of adult homozygous animals, this procedure takes 35 days to complete. 7 days are required to acclimate adult fish to 37°C and 28 days are required for engraftment studies. Our protocol provides a comprehensive guide for using immune compromised zebrafish for xenograft cell transplantation and credentials the model as a new preclinical drug discovery platform.